السياسة البيئية الج ا زئرية في مواجية التغيي ا رت المناخية - بن عيشة, علاء الدين; ربحي, ابراهيم (University of Eloued جامعة الوادي, 2023)
تعد الظاىرة المناخية ظاىرة اجتماعية عالمية ليا تأثي ا رت فادحة عمى النظام البيئي وخاصة الموارد الطبيعية المحدودة، فيي اليوم تحتاج إلى نيج متعدد التخصصات مع التركيز عمى استخدام أدوات وأساليب العموم الإنسانية، والاجتماعية بطريقة صارمة ومنيجية، بعدما فشمت جل الاست ا رتيجيات والمقاربات الأحادية، والتقنية والقانونية، في الحد من الانبعاثات الغازية والتخفيف من تأثيرىا عمى النظم البشرية، والطبيعية، خاصة أن كل المؤش ا رت الإحصائية تتجو خطيا نحو تسجيل أعمى مستويات التدمير. ومن بين الأض ا رر البيئية لمتموث حدوث ظاىرة التغير المناخي، وىو أحد المشاكل العويصة التي تواجو البشرية في ىذا العصر نتيجة لاستخدام أنواع الطاقة. وتعد التغي ا رت المناخية محو ا ر ذا أولوية قصوى في أجندة السياسة الدولية، تستمزم العمل من أجل مقاومة الانعكاسات السمبية ليا.The climate phenomenon is a global social phenomenon that has severe effects on the environmental system, especially the limited natural resources. Today, it needs a multidisciplinary approach with a focus on using the tools and methods of the humanities and social sciences in a strict and systematic manner, after most of the unilateral strategies and approaches, technical and legal, failed to limit of gaseous emissions and mitigating their impact on human and natural systems, especially since all statistical indicators tend linearly towards recording the highest levels of destruction. Among the environmental damages of pollution is the occurrence of climate change, which is one of the difficult problems facing humanity in this era as a result of the use of energy types. Climate change is a top priority on the international policy agenda, which requires action to combat its negative repercussions.
مذكرة ماستر
Keywords: التغي ا رت المناخية، التدابير، السياسة البيئية; climate change, measures, environmental policy.